Atmospheric particulate-bound mercury (PBM10) in a Southeast Asia megacity: Sources and health risk assessment. (November 2022) - Nguyen, Ly Sy Phu; Hien, To Thi; Truong, Minh Tri; Chi, Nguyen Doan Thien; Sheu, Guey-Rong
Abstract: Particulate-bound mercury (PBM) is a global environmental concern owing to its large dry deposition velocities and scavenging coefficients, both of which drive Hg into terrestrial and marine ecosystems. PBM observation studies have been widely conducted over East Asia, but comparable studies in Peninsular Southeast Asia (PSEA) remain scarce. This is the first study reporting PBM concentrations for Ho Chi Minh City (HCMC), the biggest metropolitan area in Vietnam. A total of 222 samples were collected in 2018 and contained an average PBM10 (particulate matter – PM with diameter ≤10 μm) concentration and Hg mass fraction (i.e. PBM/PM) of 67.3 ± 45.9 pg m −3 and 1.18 ± 1.12 μg g −1, respectively. Although PBM concentration was lower than those reported in Chinese megacities, the Hg mass fraction was similar to those in China, suggesting strong enrichment from anthropogenic Hg emissions in HCMC. Traffic-induced particulate emission and deposition processes were major factors governing PBM temporal variation at our site. In addition, the prevailing southwest monsoon winds brought air masses that passed through industrial areas and were associated with a higher Hg mass fraction. Statistically significant positive correlations (R 2 = 0.11–0.52, p < 0.01) were observed for PBM with PM and the Hg mass fraction, indicating similar PM and Hg sources or oxidized Hg adsorption onto PM via gas-particle partitioning. Moreover, PCA results revealed a higher contribution of primary sources than secondary sources to PBM concentration variability in HCMC. A health risk assessment indicated that the PBM concentrations at HCMC posed minimal non-carcinogenic risks (HI < 1) for children and adults, but dermal contact may act as an important exposure route since lightweight clothing is common among residents. This PBM dataset over PSEA, a region with high atmospheric Hg emissions, provides a valuable resource for the Hg scientific community to improve our understanding of Hg biogeochemical cycle. Graphical abstract: Image 1 Highlights: First groundwork PBM study in Vietnam and Peninsula Southeast Asia (PSEA). PBM temporal variation and its driving mechanisms were explored. Both primary and secondary sources could contribute to PBM variations in HCMC. T is important driver of Hg content (PBM/PM) via gas-particle partitioning process. Set up foundation for upcoming studies and improve atmospheric Hg knowledge in PSEA.